SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN FITNESS CENTRE TERBAIK MENGGUNAKAN METODE COMPLEX PROPORTIONAL ASSESSMENT - Aurianda, Rieke; Sihombing, Volvo; Juledi, Angga Putra (Politeknik Bisnis Indonesia, 2024)
This study aims to design and implement a Decision Support System (DSS) to help the people of Bagan Batu Regency in choosing the best fitness center. The increasing awareness of a healthy lifestyle has triggered the development of the fitness industry, but the many choices often make it difficult for people to determine the right choice. The Complex Proportional Assessment (COPRAS) method is used in this study because of its ability to evaluate various alternatives based on benefit and cost criteria. Five criteria are considered, namely sports facilities, instructor quality, operating hours, membership fees, and location. Data were collected from several fitness centers in Bagan Batu and processed through a normalization and weighting process. Based on the results of data processing using this method, recommendations for the best fitness centers were obtained, namely FC_04, FC_08, and FC_07. The results of this study indicate that the COPRAS method can simplify and accelerate the provision of recommendations for selecting the best fitness location in Bagan Batu Regency.